(untitled) - Vandenbosch, Betty (San Francisco, 2003)
The book presents a rational approach to juggling quality and cost factors when problem-solving business situations. Author applies diagnostic hypotheses to project planning, emphasizing client goals and relationships rather than the problem or problem-solver's expertise. Appendices detail process mapping and interviewing as solution design tools. Some real world examples are included but not extended case studies. CD-ROM contents are not specified. (booknews.com)
Keywords: Problem solving,Management,Business consultants